Sustainable rice yield improvement programme in Merbok, Kedah - Oslan, Nur Lyana Farhan; Mohd Fesool, Mohd Fahmi; Jusop, Shamshuddin; Othman, Radziah; Ishak, Che Fauziah; Man, Norsida (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Development of Kedah as a state in northern Peninsular Malaysia occurs rapidly when switching pattern of its economic base from trading to agriculture base, especially rice farming. Therefore, Merbok was chosen as the site for carrying out the study because it is outside the area of paddy granaries. However, it still contributes to the higher yield. Thus, knowledge transfer program (KTP) was carried out to help preserve more agricultural fields in the area. Program carried out by selecting four (4) farmers and take at least 0.7 ha to 1.4 ha of each participant to be a demo plot. Knowledge transfer program started from September, 2012 and will end in August, 2014 include seminars, advisory services in collaboration with farmers in Merbok. The method of used beneficial microbes (bio-fertilizer) and lime (GML). Expected results of the program is that farmers become more knowledgeable in rice production resulting in increase income.